2020
DOI: 10.1371/journal.pone.0233685
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and anatomical examination of normal thyroid and internal parathyroid glands in goats

Abstract: Ultrasonographic examination of the normal thyroid and parathyroid glands has been described for humans and many animal species. However, similar reports for goats are still missing. The aim of the study was to present ultrasound features of the normal thyroid and internal parathyroid glands in goats with the determination of their dimensions and volume, followed by a comparison of the results to the gross examination. Seventy-two goats were used in the study. The echostructure and echogenicity of the thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…Few differences between left and right lobes were observed in other studies in calves [ 34 ], dogs [ 25 ] and horses [ 29 ]. Another study did not notice any difference between the two lobes during TU on goats [ 30 ]. Although our population size is sufficient to assess intra-/inter-observer variation for TU, it is insufficient to make clear conclusions about normal ultrasound dimensions of the thyroid gland in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few differences between left and right lobes were observed in other studies in calves [ 34 ], dogs [ 25 ] and horses [ 29 ]. Another study did not notice any difference between the two lobes during TU on goats [ 30 ]. Although our population size is sufficient to assess intra-/inter-observer variation for TU, it is insufficient to make clear conclusions about normal ultrasound dimensions of the thyroid gland in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…In ruminants, two studies [ 30 , 31 ] have recently studied the ultrasonographic, anatomical examination and Computed Tomography Scanner appearance of normal thyroid in goats. One of these studies has concluded that the thyroid gland is clearly visible in all the goats in the study and identified a standard TU measurement for goats [ 30 ]. No significant difference was found between the two lobes.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid volume was estimated using the formulae previously validated in humans (a) [ 7 ], dogs (a) [ 9 ] and goats (b) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Składa się z dwóch płatów umiejscowionych symetrycznie po obu stronach tchawicy i połączonych ze sobą po dobrzusznej stronie tchawicy słabo wykształconą włóknistą cieśnią. Oba płaty są zbliżonej wielkości (długość ok. 3 cm, szerokość ok. 1 cm i grubość ok. 0,6 cm) (28,29).…”
Section: Gruczoł Tarczowyunclassified